THE EFFECT OF LECTURER’S PROFESSIONALISM AND STUDENT’S STUDY INTEREST AND MOTIVATION ON ACADEMIC ACHIEVEMENT OF BACHELOR DEGREE STUDENT IN ONLINE LEARNING IN BINUS UNIVERSITY - Trivena, Trivena; Harisno, Harisno (Bina Nusantara University, 2014)
Online learning is a learning method that doesn’t close any possibility can be run with collaboration between learning asynchronous and synchronous model. This research is to find out whether lecturer’s professionalism and student’s interest and study motivation give significant effect to academic achievement of bachelor degree online learning in BINUS university either concurrent or partial. Sampling technique that is used is random sampling, and used sample is about 99 samples of active student. Hypothesis testing that is done using one lane analysis model, where analysis is done using regression analysis test and corelation analysis test either concurrent or partial. The result of this research can be concluded that there is significant effect between lecturer’s professionalism, student’s interest and motivation with student’s academic achievement either partial or concurrent. This research result is hoped to be able to give benefit to BINUS University, so it can be suggestion in developing teaching and learning system in BINUS online learning by paying attention to external and internal factors that affect and increase student’s academic achievement.